2006
DOI: 10.1111/j.1530-0277.2006.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the History of Conduct Disorder on the Iowa Gambling Tasks

Abstract: These results indicate that the history of conduct disorder may contribute to impaired decision making on GT. Furthermore, this kind of decision-making pattern may represent one of common underlying mechanisms in both conduct disorder and alcohol dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…First, previous studies show that performance on the IGT is impaired in young people with antisocial personality (Mazas, Finn, & Steinmetz, 2000), conduct disorder (Kim, Lee, & Kim, 2006) and early-onset schizophrenia (Kester et al, 2006). We measured a number of psychological factors potentially related to smoking, including hostility, aggressiveness, sensation-seeking, Attention Deficit Hyperactivity Disorder (ADHD), depression, perceived stress, and impulsivity, but we did not find any confounding effect by those variables.…”
Section: Limitationsmentioning
confidence: 79%
“…First, previous studies show that performance on the IGT is impaired in young people with antisocial personality (Mazas, Finn, & Steinmetz, 2000), conduct disorder (Kim, Lee, & Kim, 2006) and early-onset schizophrenia (Kester et al, 2006). We measured a number of psychological factors potentially related to smoking, including hostility, aggressiveness, sensation-seeking, Attention Deficit Hyperactivity Disorder (ADHD), depression, perceived stress, and impulsivity, but we did not find any confounding effect by those variables.…”
Section: Limitationsmentioning
confidence: 79%
“…In contrast, Goudriaan et al did not find difference between alcohol-dependent patients who had been abstinent for a period of 3-12 months and controls on any measures of the WCST 27 . Studies with non-abstinent alcohol subjects have also shown impairment in performance relative to controls on the IGT 22,28,29 (but see 30,31 ) and the WCST, as well as other set-shifting types of tasks 28,31 . In sum, results from the literature are in accordance with ours to the extent that most of them showed impairments among alcoholdependent subjects on behavioral tests that assess motor, nonplanning and cognitive/attention dimensions of impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy for assessing impulsivity and its relation to decision-making in patients with BD has been the structured Iowa Gambling Task (IGT) (Bechara et al, 1994, Clark et al, 2001, Kim et al, 2006) (Table 1). In the IGT, participants have to select the best of four options varying both the size and probability of the reward and loss (Bechara et al, 1997, 2005).…”
Section: Genetic Models Of Bipolar Maniamentioning
confidence: 99%